Toward a Single Reed Mouthpiece for the Oboe - CARRAL, Sandra; VERGEZ, Christophe; NEDERVEEN, Cornelis J. (Archives of Acoustics, 2011)
Reed woodwind instruments differ in both their geometry (mainly cylindricalor mainly conical) and their excitation mechanism (single or double reed). Howmuch of the resulting sound is due to the single/double reed, and how much to thegeometry of the instrument? Measurements done by Almeida et al. (J. Acoust. Soc.Am., 121, 1, 536–546, 2007) show that the flow vs pressure characteristic curve ofan oboe reed is not that different from that of a clarinet reed, the only differenceprobably being due to pressure recovery inside the conical staple. Is it possible tomake a single reed mouthpiece for an oboe, while keeping the conical staple, thatwould still give the oboe its characteristic sound? To find it out, a mouthpiece withthe following characteristics was made: A standard clarinet B[ reed can be attachedto it, its volume is approximately that of the missing part of the instrument cone,and a standard French oboe staple can be inserted to it, so that it can be inserted inthe usual way in any french oboe. In this paper, the first prototype of the mouthpieceis shown. Also, a sound comparison of the oboe sounds played with this mouthpieceand a standard double reed by a professional player is presented.